Erodabilidad y erosión hídrica potencial en un sector de la cuenca del rio Otún - Colombia - Madero Morales Edgar Enrique; Bergsma Eelco (Acta Agronómica)
The present research seeks to determine the applicability of simple, rapid and economic methods tor comparing the soil erodability under twelve cultivation systems, and besides to record the features of rill erosion under ale crops in the watershed area of the Otún river. Here the denudation processes are common and affect a large portion of the area. The erodability tests considered (crumb, pinhole, manipulation, rain acceptance, soil loss, shear strenght) are related to soil toss with reference to erodable material and the volume of surface flow. These do not seek to quantify the actual or potential soil loss of a place, but can help in the estimation of the variability of soil erodability with the content of surface gravel, the state soil moisture content and time. To predict the advance of rill and interril erosion in bare soil, Bergsma (1989) developed a semicuantitative system with this purpose, and what is related to the presence and frequency of six microtopography soil surface features after each rain and at the end of tillage: original clods, eroding clods, depressional areas, linear flow pattern of shallow channels and deeper rills, and coverage (vegetation, gravel, etc.); each feature has a length less than 25 cm. The erodability tests demonstrate their practical value with no more than three repetitions per unit of management. There was more soils (8/12) with low erodability. The evolution of microtopograhy soil surface features showed that corn, bean and grass increased depressional areas and shallow channels; the tendency in onion was similar but with a relatibility increase in deeper rills. Bean and grass crops were the less erosion hazard uses because they let a few loss of soil at the more inestable terrains. Contrary, corn and onion are not the most recomendable uses because they allowed the biggest advance of erosion in the most stable soils. Las pruebas de erodabilidad consideradas (terrón, agujero, manipulación o textura, aceptación de lluvia, efecto torsional, pérdida de suelo real y con pendiente del 9%, surcamiento) tienen relación con las pérdidas de suelo en lo referente a Material Erodable y a Volumen de Flujo Superficial; no pretenden cuantificar las pérdidas actuales o potenciales de un lugar, pero pueden servir como estimativos de la variabilidad del factor K en función de la labranza, del contenido de grava superficial, del estado de humedad del suelo y del tiempo. Para predecir el avance de la erosión laminaren porciones de suelo desnudo, Bergsma (1989) propuso un sistema semicuantitativo, cuyo principio consiste en determinar la frecuencia de aparición de seis rasgos micro topográficos superficiales después de cada lluvia y a partir de la última labor de preparación: peds resistentes, superficies erodadas, superficies de flujo, presurcos y surcos, depresiones y vegetación o piedras; la extensión de cada rasgo no pasa de 25 cm. La densidad mínima de observaciones demostró el valor práctico de las pruebas de erodabilidad requiriéndose no más de tres repeticiones por unidad de manejo. Hubo mayor proporción de suelos (8 de 12) con baja erodabilidad. La evolución de los rasgos micro topográficos superficiales reveló que en maíz, frijol y pasto de corte aumentaron paulatinamente las superficies de flujo y los presurcos; la tendencia en cebolla fue similar pero con incremento relativo de los surcos. Los sistemas de cultivo de frijol y pasto de corte fueron los de menor riesgo de erosión hídrica dado que permitieron poca pérdida de suelo en los terrenos más inestables; los de maíz y cebolla permitieron el mayor avance de la erosión en los suelos más estables.